2020
DOI: 10.3390/nu12082194
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of a Polyphenol-Rich Leaf Extract of Mangifera indica L. (Zynamite) on Cognitive Function in Healthy Adults: A Double-Blind, Placebo-Controlled Crossover Study

Abstract: Extracts made from the leaves of the mango food plant (Mangifera indica L., Anacardiaceae) have a long history of medicinal usage, most likely due to particularly high levels of the polyphenol mangiferin. In rodent models, oral mangiferin protects cognitive function and brain tissue from a number of challenges and modulates cerebro-electrical activity. Recent evidence has confirmed the latter effect in healthy humans following a mangiferin-rich mango leaf extract using quantitative electroencephalography (EEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
4
27
0
Order By: Relevance
“…Butyrate producers, such as Eubacterium , contribute to the SCFAs pool and the modification of various signaling pathways involving G-protein-coupled receptors and the inhibition of histone deacetylases [ 72 ]. Furthermore, many polyphenolic compounds of Mangifera indica and metabolites thereof have been described to improve the cognitive function of learning and memory function as well as areas of cognitive impairment [ 73 , 74 ]. Specifically, gallic acid—the product of gallotannin hydrolysis and mangiferin, a c-glucosyxanthone (C2-β- d -glucopyranosyl-1,3,6,7-tetrahydroxyxanthone) capable of crossing the blood–brain barrier—has been the main target of these studies.…”
Section: Interactions Between Mango Polyphenols and The Intestinal Microbiotamentioning
confidence: 99%
“…Butyrate producers, such as Eubacterium , contribute to the SCFAs pool and the modification of various signaling pathways involving G-protein-coupled receptors and the inhibition of histone deacetylases [ 72 ]. Furthermore, many polyphenolic compounds of Mangifera indica and metabolites thereof have been described to improve the cognitive function of learning and memory function as well as areas of cognitive impairment [ 73 , 74 ]. Specifically, gallic acid—the product of gallotannin hydrolysis and mangiferin, a c-glucosyxanthone (C2-β- d -glucopyranosyl-1,3,6,7-tetrahydroxyxanthone) capable of crossing the blood–brain barrier—has been the main target of these studies.…”
Section: Interactions Between Mango Polyphenols and The Intestinal Microbiotamentioning
confidence: 99%
“…An extensive range of compounds found in Mangifera indica L., leaves, seeds or even tree bark have been extensively used in traditional medicine for the treatment of different diseases [ 20 , 24 , 25 , 26 ]. One of the most relevant compounds in mango leaves is mangiferin, not only for its high proportion, but also for its antioxidant and anti-inflammatory capacities [ 26 , 27 , 28 ], which have been endorsed by both in vitro and in vivo experiments [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive range of compounds found in Mangifera indica L., leaves, seeds or even tree bark have been extensively used in traditional medicine for the treatment of different diseases [ 20 , 24 , 25 , 26 ]. One of the most relevant compounds in mango leaves is mangiferin, not only for its high proportion, but also for its antioxidant and anti-inflammatory capacities [ 26 , 27 , 28 ], which have been endorsed by both in vitro and in vivo experiments [ 29 , 30 , 31 ]. For instance, mangiferin has exhibited anti-inflammatory responses against different inflammation mechanisms, such as the inhibition of nitrogen monoxide production, which cause blood vessels dilatation [ 30 ], or the inhibition of some pro-inflammatory factors such as interleukin-1 (IL-1 ) [ 32 , 33 , 34 ], or tumor necrosis factor (TNF- ) [ 31 , 35 ], both of which play an important role during the acute phase of inflammation processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue on "Dietary Polyphenols and Human Health", a series of 10 papers are presented, including three literature reviews [6][7][8] and seven original research papers [9][10][11][12][13][14][15]. The described research contributes to filling some of the gaps in our knowledge about the beneficial effects of dietary polyphenols on chronic health conditions, notably cardiovascular disease, type 2 diabetes, neurological impairment, and also certain risk factors.…”
mentioning
confidence: 99%
“…In a study on psychological well-being (the PPhIT study), Kontogianni et al concluded that participants with a high polyphenol intake had fewer depressive symptoms and better general mental and physical health compared to those on a low-phenolic diet [10]. The crossover study on mood and cognitive function performed by Wightman et al, where healthy participants received a single dose of a polyphenol-rich extract obtained from mango leaves (<60% mangiferin), revealed no significant results for mood, but cognitive function was enhanced [11].…”
mentioning
confidence: 99%